Calculation and Analysis of Power Loss in the Drive Axle of High-power Loaders - Chen Sujiao; Zhang Senbo; Zhang Hanyu; Liang Xinghua; Qian Xu; Liu Chunbao; Xu Wenbo (Jixie chuandong)
In high power loaders, the drive axle is a key part of the drive train and its low power loss is critical to maintain consistently excellent performance. Calculating its power loss is challenging due to the complexity of its internal structure. A platform for calculating the power loss of the drive axle including the main reducer, the brake and the wheel-edge reducer was constructed in the Matlab platform, and the distribution of various power losses in the drive axle was obtained, while the accuracy of the calculation platform was verified accordingly through experiments. The results show that the calculation error is within 12%. The proposed modeling method and results provide important reference for the rapid and low-cost development of new generation drive axle products.